The potential of glucagon-like peptide-1 receptor agonists in heart failure - Kreiner, Frederik Flindt; Hovingh, G. Kees Kornelis; von Scholten, Bernt Johan (Frontiers in Physiology, 2022)
Heart failure (HF) remains one of the cardiovascular diseases (CVDs) associated with a high unmet medical need due to high morbidity and mortality rates and lack of efficacious interventions. HF is closely related to cardiometabolic diseases such as diabetes, obesity and chronic kidney disease, and strategies that address most or all these intertwined conditions are desirable. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are approved for type 2 diabetes (T2D), and some are also indicated for reduction of the risk of atherosclerotic CVD in T2D and for weight management. As we summarise in this concise review, preliminary evidence suggests that the cardioprotective benefits of GLP-1 RAs may also extend to HF. The most robust clinical evidence arguably originates from the large cardiovascular outcomes trials (CVOTs) completed for most GLP-1 RAs, of which the latest showed a significant relative risk reduction (RRR) of 39% (HR) with once-weekly efpeglenatide on HF requiring hospitalisation, corroborating a meta-analysis which found a significant RRR across eight GLP-1 RA CVOTs of 11%. Further, although incompletely described, multiple studies are available to provide insights into the mechanistic underpinnings, which appear to be associated mostly with indirect cardioprotective benefits owing to the ability of GLP-1 RAs to address hyperglycaemia, and reduce body weight, and, amongst others, inflammation. In sum, current evidence positions GLP-1 RAs as a potential cardioprotective strategy in HF, with HF with preserved ejection fraction emerging as the clinically most relevant phenotype for the drug class, especially when occurring in people with obesity with and without diabetes.